Sprachwissenschaft im Fokus: Positionsbestimmungen und Perspektiven ; [50. Jahrestagung des Instituts für Deutsche Sprache, Mannheim 11. - 13. März 2014] - Eichinger, Ludwig M. (Jahrbuch ..., 2015)
The contributions of this volume, celebrating the 50th anniversary of Institut für deutsche Sprache, discuss current trends in grammar research and grammaticography, lexicology and lexicography, spoken language research, as well as corpus and computer linguistics. In addition, they provide an overview of the current status of linguistic research and possible new fields of investigation --
Literaturangaben
Keywords: Konferenzschrift -- 2014 -- Mannheim; Aufsatzsammlung; Linguistik; Germanistik; Deutsch